At Term, XmO and XpO Mouse Placentas Show Differences in Glucose Metabolism in the Trophectoderm-Derived Outer Zone - He, Nannan; Lim, Shujing J.; Moreira de Mello, Joana C.; Navarro, Injerreau; Bialecka, Monika; Salvatori, Daniela C. F.; van der Westerlaken, Lucette A. J.; Pereira, Lygia V.; Chuva de Sousa Lopes, Susana M. (Frontiers in Cell and Developmental Biology, 2017)
Genetic mouse model (39,XO) for human Turner Syndrome (45,XO) harboring either a single maternally inherited (Xm) or paternally inherited (Xp) chromosome show a pronounced difference in survival rate at term. However, a detailed comparison of XmO and XpO placentas to explain this difference is lacking. We aimed to investigate the morphological and molecular differences between XmO and XpO term mouse placentas. We observed that XpO placentas at term contained a significantly larger area of glycogen cells (GCs) in their outer zone, compared to XmO, XX and XY placentas. In addition, the outer zone of XpO placentas showed higher expression levels of lactate dehydrogenase (Ldha) than XmO, XX and XY placentas, suggestive of increased anaerobic glycolysis. In the labyrinth, we detected significantly lower expression level of trophectoderm (TE)-marker keratin 19 (Krt19) in XpO placentas than in XX placentas. The expression of other TE-markers was comparable as well as the area of TE-derived cells between XO and wild-type labyrinths. XpO placentas exhibited specific defects in the amount of GCs and glucose metabolism in the outer zone, suggestive of increased anaerobic glycolysis, as a consequence of having inherited a single Xp chromosome. In conclusion, the XpO genotype results in a more severe placental phenotype at term, with distinct abnormalities regarding glucose metabolism in the outer zone.